CLIL: SUGGESTED ENGLISH MATERIALS FOR CURRICULUM 2013 - Prasetianto, Mushoffan (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2014)
Teaching approaches always change from time to time. The change of teaching approaches is followed by the change of materials. The new materials in secondary level are Content and Language Integrated Learning (CLIL). From these materials, the students are expected to be able to understand other subjects which are written in English. In secondary level, the subjects are science and mathematics. Thus, this paper provides materials, teaching procedures of CLIL and SWOT analysis. The materials are related to the science theme. There are three topics under science theme: digestive system, laboratory equipments and symbols, and light. The teaching procedure of CLIL is Presenting, Practicing and Producing (PPP). Firstly, the teacher presents the material. Secondly, the students practice to retell the material. Lastly, the students produce wall-magazine, posters and experiment report. In conclusion, CLIL materials can be explored more by English teachers because it is new and interesting.